PENERAPAN AKUNTANSI PERSEDIAAN SESUAI DENGAN PSAK NO.14 PADA PT PERTANI PERSERO CABANG PINRANG - Rahma, Rika (Economos : Jurnal Ekonomi dan Bisnis, 2021)
One of the factors that play an equally important role in achieving company goals as expected is inventory. It is because most of the company's activities are related to inventory. This research aim is to know the application of inventory accounting that has followed PSAK No. 14. The research used data collection techniques of observation, documentation, and interviews. The research design was descriptive qualitative research with a comparative approach which aims to find out or describe and compare the reality of the events being studied that make it easier to obtain objective data to know and understand the application of inventory accounting following PSAK No. 14. Data analysis technique was conducted by comparing the reality with the condition of an object and then interpreting it to provide a clear picture of the problems regarding the application of inventory accounting with PSAK No. 14. The research results explained that in general the implementation of inventory accounting treatment at PT. Pertani (Persero) UPA Pinrang Unit has complied with the implementation of inventory accounting treatment according to Financial Accounting Standards Number 14 of 2012.